Targeting digestive system cancers with isoliquiritigenin: a comprehensive review of antitumor mechanisms - Li, Zhichun; Feng, Ruohan; Li, Jinze; Bai, Jinglu; Li, Nuo; Cui, Zhenhua; Zhang, Xiaobin (Frontiers in Pharmacology, 2025)
Digestive system malignancies, including gastric, colorectal, and liver cancers, account for a substantial proportion of global cancer morbidity and mortality. Despite advancements in conventional treatment strategies such as chemotherapy, radiotherapy, surgical resection, and immunotherapy, clinical outcomes remain unsatisfactory due to limited therapeutic efficacy, severe side effects, and poor patient prognosis. Therefore, the development of more effective and less toxic treatment options is urgently needed. Isoliquiritigenin (ISL), a natural chalcone-type flavonoid primarily extracted from licorice (Glycyrrhiza spp.), has attracted increasing attention for its broad pharmacological properties, including anti-inflammatory, antioxidant, antiviral, and anticancer activities. Recent studies have revealed the potential of ISL to modulate multiple signaling pathways and cellular processes involved in tumorigenesis, such as apoptosis, autophagy, ferroptosis, cell cycle regulation, and immune modulation. This review comprehensively summarizes the current understanding of ISL’s anticancer mechanisms in digestive system tumors, highlighting its multi-targeted actions and potential as a promising therapeutic agent. The findings aim to provide valuable insights for future preclinical studies and clinical applications.